Pediatric Resident Experience Caring for Children at the End of Life in a Children’s Hospital - Trowbridge, Amy (Acad Pediatr, 2019)
OBJECTIVE: Pediatric residents are expected to be competent in end-of-life (EOL) care. We aimed to quantify pediatric resident exposure to patient deaths, and the context of these exposures. METHODS: Retrospective chart review of all deceased patients at one children’s hospital over 3 years collected patient demographics, time, and location of death. Mode of death was determined after chart review. Each death was cross-referenced with pediatric resident call schedules to determine residents involved within 48 hours of death. Descriptive statistics are presented. RESULTS: Of 579 patients who died during the study period, 46% had resident involvement. Most deaths occurred in the NICU (30% of all deaths); however, resident exposure to EOL care most commonly occurred in the PICU (52% of resident exposures) and were after withdrawals of life-sustaining therapy (41%), followed by nonescalation (31%) and failed resuscitation (15%). During their postgraduate year (PGY)-1, <1% of residents encountered a patient death. During PGY-2 and PGY-3, 96% and 78%, respectively, of residents encountered at least 1 death. During PGY-2, residents encountered a mean of 3.5 patient deaths (range 0–12); during PGY-3, residents encountered a mean of 1.4 deaths (range 0–5). Residents observed for their full 3-year residency encountered a mean of 5.6 deaths (range 2–10). CONCLUSIONS: Pediatric residents have limited but variable exposure to EOL care, with most exposures in the ICU after withdrawal of life-sustaining technology. Educators should consider how to optimize EOL education with limited clinical exposure, and design resident support and education with these variable exposures in mind.